Are front crawl upper limbs coordination and kinematics affected by parachutes sizes? - Salgueiro, D. F.; Barroso, R.; Telles, T.; Fernandes, R. J.; Andries Jr, O. (Medicina dello Sport, 2020)
BACKGROUND: The aim of the current study was to investigate the acute effects of different parachutes sizes on index of coordination and kinematics of competitive front-crawl male swimmers. METHODS: Ten male competitive swimmers (19±1 years old and 27.18±1.49s of 50 m freestyle short course best time) volunteered to participate. Experiments consisted of maximal and randomized 4 x 25m front crawl (10 min intervals) in free swimming and using small, medium and large sizes parachutes (288, 400 and 900 cm2). All trials were recorded by two 60 Hz synchronized video cameras to assess average speed, stroke rate, stroke length, upper limbs phases and index of coordination. RESULTS: Swimming speed (-10.9, -18.3 and -32.7%), stroke rate (-7.0, -9.4 and -13.2%) and stroke length (-4.2, -9.9 and -22.5%) decreased according to the small, medium and large parachute sizes compared to free swimming. The relative duration of the pull phase was reduced when using small and medium sizes parachutes (25.2±1.7 and 25.4±1.7%) and the push phase increased in all conditions (24.0±2.6, 24.9±2.3 and 25.3±2.5%) compared to free swimming. Parachute swimming did not induce statistical changes on the index of coordination but, from a practical point of view, the coordination mode changed from opposition to superposition when using the large parachute. CONCLUSIONS: Swimmers with a catch-up coordination seem to benefit from the parachute use to change coordination mode and improve propulsive continuity. Coaches should adapt the parachute size individually and evaluate its effects.